2021
DOI: 10.3390/nu13072268
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PI3K/Akt Signaling Pathway in Rat Hypothalamus Induced by an Acute Oral Administration of D-Pinitol

Abstract: D-Pinitol (DPIN) is a natural occurring inositol capable of activating the insulin pathway in peripheral tissues, whereas this has not been thoroughly studied in the central nervous system. The present study assessed the potential regulatory effects of DPIN on the hypothalamic insulin signaling pathway. To this end we investigated the Phosphatidylinositol-3-kinase (PI3K)/Protein Kinase B (Akt) signaling cascade in a rat model following oral administration of DPIN. The PI3K/Akt-associated proteins were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…These data also point to a regional specificity of the actions of DPIN on both tau phosphorylation and brain insulin signalling. Thus, we did not detect changes in the hypothalamus nor in the temporal cortex of the Wistar rats treated with DPIN for 10 days (Figure S3), whereas we did observe a clear activation of PI3K/Akt signalling pathway in the hypothalamus after DPIN administration (Medina‐Vera et al, 2021).…”
Section: Discussionmentioning
confidence: 64%
“…These data also point to a regional specificity of the actions of DPIN on both tau phosphorylation and brain insulin signalling. Thus, we did not detect changes in the hypothalamus nor in the temporal cortex of the Wistar rats treated with DPIN for 10 days (Figure S3), whereas we did observe a clear activation of PI3K/Akt signalling pathway in the hypothalamus after DPIN administration (Medina‐Vera et al, 2021).…”
Section: Discussionmentioning
confidence: 64%
“…In recent years, d -pinitol has been used as a bioactive compound for many diseases, especially diabetes ( 29 , 30 , 56 ). Oral ingestion of d -pinitol significantly improves the insulin-glucose metabolic homeostasis of diabetic patients, streptozotocin-diabetic rats, and glucose-loaded mice ( 32 , 33 , 57 , 58 ). Further studies showed that d -pinitol acts through the phosphatidylinositol 3-kinase/protein kinase B ( PI3K / Akt ) pathway ( 57 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB induces the synthetic phenotype in VSMCs via an extracellular signal-regulated kinase (ERK) and phosphatidylinositol 3-kinase/Akt (PI3K/AKT)-mediated pathway, resulting in reduced ACTA2 and SM22α activity (36), suggesting that PI3K activity maybe increased in Sema3f -/- VSMCs. Indeed, phospho-PI3K p85α (Tyr607), a marker of PI3K activity (37), was increased in vivo in lesional αSMA-positive Sema3f -/- VSMCs ( Sema3f +/+ : 39.8±4.7, n=3; Sema3f -/- : 63.9±2.0, n=5; phospho-PI3K expression (% of mature SMCs), p=0.001, Figure 5F), suggesting that SEMA3F-mediated modulation of PI3K activity may contribute to the pro-atherogenic VSMC phenotypes in Sema3f -/- mice.…”
Section: Resultsmentioning
confidence: 99%